2007
DOI: 10.1111/j.1742-4658.2007.05767.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a eugenol oxidase from Rhodococcus sp. strain RHA1

Abstract: The flavoenzyme vanillyl alcohol oxidase (VAO, EC 1.1.3.38) from Penicillium simplicissimum is active on a range of phenolic compounds [1,2]. It contains a covalently linked FAD cofactor, and the holoprotein forms stable octamers. VAO was the first histidyl-FAD-containing flavoprotein for which the crystal structure was determined [3], and serves as a prototype for a specific flavoprotein family [4]. Mutagenesis studies have shown that the covalent flavin-protein bond is crucial for efficient catalysis, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 30 publications
5
80
0
3
Order By: Relevance
“…eugenol oxidase. For this enzyme, it was observed that incomplete FAD incorporation leads to the presence of apoenzyme rather than ADP-containing protein (19). This strongly suggests that incorporation of ADP in PuO Rh is likely to be the result of a competition between FAD and ADP binding, both being present in the cytoplasm.…”
Section: Discussionmentioning
confidence: 95%
“…eugenol oxidase. For this enzyme, it was observed that incomplete FAD incorporation leads to the presence of apoenzyme rather than ADP-containing protein (19). This strongly suggests that incorporation of ADP in PuO Rh is likely to be the result of a competition between FAD and ADP binding, both being present in the cytoplasm.…”
Section: Discussionmentioning
confidence: 95%
“…However, only a few GMC oxidoreductases can oxidize alcohols to the corresponding carboxylic acids (12,15). Although hydroxylations and amine oxidations have been described for other types of flavoprotein oxidases (16), thus far, no GMC flavoprotein oxidases with such activities have been identified (10).…”
mentioning
confidence: 99%
“…The eugenol catabolic pathway is substantiated by a previous characterization of eugenol oxidase (39). Nevertheless, the induction of these genes by ferulate is unexpected.…”
Section: Discussionmentioning
confidence: 60%
“…The first gene, eugO, encodes eugenol oxidase. This enzyme has been purified from RHA1 and oxidizes eugenol to coniferyl alcohol (39). Coniferyl alcohol is presumably oxidized to coniferyl aldehyde and then to ferulate (40).…”
Section: Growth Of Rha1 On P-hydroxycinnamatesmentioning
confidence: 99%